Family law for non-Muslims in Malaysia: development and reforms - Ibrahim, Norliah; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Md Hashim, Noraini; Mohd, Azizah; Abd Malek, Normi; Mohd Kamal, Mohd Hisham (s.n, 2012)
The research clarifies the ambiguities and proposes suggestions to overcome weaknesses and loopholes in the law.